Handbook for social workers on basic bio-psychosocial help for children in need of special protection - De Castro, Elizabeth Protacio ([Quezon City] Center for Integrative and Development Studies. University of the Philippines, 2001)
This book aims to introduce the social workers to children in need of special protection (CNSP) and bio-psychosocial help. It contains guidelines, tool and techniques in helping CNSP. It was published so that social workers will become more efficient and effective in handling cases of CNSP.
Contents: Introduction and orientation to children in need of special protection and bio-psychosocial help. Guidelines in helping children in need of special protection. Tools and techniques for helping CNSP.
Purpose: "An easy guide for social workers and service providers in providing bio-psychosocial interventions for children and their families. It enhances their understanding on their roles as service providers at the same time helps them build their capabilities to become more efficient and effective."
Keywords: Child welfare -- Philippines; Social work with children -- Philippines; Children -- Services for -- Philippines; Child care -- Philippines -- Handbooks, manuals, etc